2007
DOI: 10.1111/j.1471-4159.2007.05153.x
|View full text |Cite
|
Sign up to set email alerts
|

Cell type‐specific subunit composition of G protein‐gated potassium channels in the cerebellum

Abstract: G protein‐gated inwardly rectifying potassium (GIRK/Kir3) channels regulate cellular excitability and neurotransmission. In this study, we used biochemical and morphological techniques to analyze the cellular and subcellular distributions of GIRK channel subunits, as well as their interactions, in the mouse cerebellum. We found that GIRK1, GIRK2, and GIRK3 subunits co‐precipitated with one another in the cerebellum and that GIRK subunit ablation was correlated with reduced expression levels of residual subunit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
111
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 69 publications
(120 citation statements)
references
References 53 publications
9
111
0
Order By: Relevance
“…Nonetheless, the DA-associated Girk2 channel [21][22][23] was detected by RT-PCR both in this study and by Atala and colleagues who also demonstrated its functionality (i.e., barium sensitivity) in culture [17]. As Girk2 expression has also been reported in a variety of non-DA neurons [24][25][26], proof that its expression here represents the acquisition of a bona fi de DA neuronal trait will require experimental corroboration by other methods. Additionally, using different AFS lines and a different DA differentiation protocol, Tsai et al [27] transcripts for nestin, β-tubulin III and FN, with no shift in the mRNA expression profi le toward a neuronal fate after further differentiation in culture.…”
Section: Discussionsupporting
confidence: 65%
“…Nonetheless, the DA-associated Girk2 channel [21][22][23] was detected by RT-PCR both in this study and by Atala and colleagues who also demonstrated its functionality (i.e., barium sensitivity) in culture [17]. As Girk2 expression has also been reported in a variety of non-DA neurons [24][25][26], proof that its expression here represents the acquisition of a bona fi de DA neuronal trait will require experimental corroboration by other methods. Additionally, using different AFS lines and a different DA differentiation protocol, Tsai et al [27] transcripts for nestin, β-tubulin III and FN, with no shift in the mRNA expression profi le toward a neuronal fate after further differentiation in culture.…”
Section: Discussionsupporting
confidence: 65%
“…EGFP expression was found in small subsets of cells in defined structures, including the substantia nigra and hippocampus ( Fig. 1 C and D), and cerebellum (13). In contrast, EGFP labeling in the hypothalamus was prominent and relatively uniform.…”
Section: Resultsmentioning
confidence: 95%
“…Histochemistry involving brain sections from adult mice (8 -10 weeks old) was performed as described in ref. 13. Images were collected by using a Bio-Rad MRC 1024 confocal laserhead on an upright microscope and an Olympus AX-70 camera with Bio-Rad LaserSharp 3.0 software.…”
Section: Table 3 Energy Expenditurementioning
confidence: 99%
“…A current with functional properties resembling those of GIRK channels has been described in dissociated UBCs (Knoflach and Kemp 1998). More recently, Harashima et al (2006) and Aguado et al (2008) have shown that mouse UBCs express the GIRK2 and GIRK3 subunits. These data raise the possibility that the currents activated in UBCs by ambient glutamate levels may be mediated by GIRK channels.…”
Section: Nature Of the Background Potassium Currentmentioning
confidence: 92%